SYMBOLS OF DOMESTIC ANIMALS IN THE UZBEK LANGUAGE: A LINGUOCULTURAL ANALYSIS (Ustozlar uchun, 2026)
This article examines the symbolic meanings of domestic animals in the Uzbek language from a linguocultural perspective. The study analyses how animals such as the horse, dog, sheep, camel, and ox function as cultural symbols in Uzbek proverbs, phraseological units, folklore, and literary texts. The research demonstrates that domestic animal symbols in Uzbek reflect the nation’s historical lifestyle, value system, and worldview.